Epithelial membrane protein 1 promotes glioblastoma progression through the PI3K/AKT/mTOR signaling pathway - Miao, Lifeng (Oncol Rep, 2019)
Glioblastoma multiforme (GBM) is the most malignant intracranial tumor. Although the affected patients are usually treated with surgery combined with radiotherapy and chemotherapy, the median survival time for GBM patients is still approximately 12–14 months. Identifying the key molecular mechanisms and targets of GBM development may therefore lead to the development of improved therapies for GBM patients. In the present study, the clinical significance and potential function of epithelial membrane protein 1 (EMP1) in malignant gliomas were investigated. Increased EMP1 expression was associated with increasing tumor grade (P<0.001) and worse prognosis in patients (P<0.001) based on TCGA, Rembrandt and CGGA databases for human gliomas. In vitro, gene silencing of EMP1 in U87MG and P3 GBM (primary glioma) cells significantly inhibited tumor proliferation and invasion. In addition, it was revealed that activation of the PI3K/AKT/mTOR signaling pathway is the driving force of EMP1-promoted glioma progression. Finally, it was demonstrated, using an intracranial GBM animal model, that EMP1 knockdown significantly inhibits tumor growth in vivo and increases overall survival in tumor-bearing animals. Our research provides new insights into the molecular mechanisms underlying EMP1 knockdown-mediated inhibition of GBM cell invasion and raises the possibility that targeting of EMP1 may represent a promising strategy for the treatment of GBM.